ISBS 2019 4th International Sustainable Buildings Symposium - Burcu Gültekin, Arzuhan (IntechOpen, 2019)
The 4th International Sustainable Buildings Symposium (ISBS 2019) (www.isbs2019.gazi.edu.tr) was held on July 18-20, 2019 in the City of Dallas, Texas, USA, in cooperation with Texas Tech University, Texas A&M University-Commerce, Ankara University, and Gazi University and in collaboration with the American Institute of Architects Dallas Chapter (AIA Dallas), and the US Green Building Council North Texas Chapter (USGBC North Texas). The North Texas Sustainable Showcase (NTSS 2019), co-organized regularly by AIA Dallas and USGBC North Texas every year, hosted the ISBS 2019 special this year.